Put in the values of a and b into the equation and work it out.
The answer is 1.
2006-09-25 20:47:58
·
answer #1
·
answered by Brenmore 5
·
0⤊
0⤋
1
2006-09-26 05:40:44
·
answer #2
·
answered by mike 2
·
0⤊
0⤋
1
2006-09-26 01:47:05
·
answer #3
·
answered by John M 2
·
0⤊
0⤋
1
2006-09-26 01:44:21
·
answer #4
·
answered by musiccross 2
·
0⤊
0⤋
x = (1 * 2 / 2) * (1 + 2 - 2) = 1 * 1 = 1
2006-09-26 01:41:21
·
answer #5
·
answered by dutch_prof 4
·
0⤊
0⤋
x=(1)(2)/2 (1+2-2)
x=(2/2)(3-2)
x=1(1)
x=1
2006-09-26 01:42:41
·
answer #6
·
answered by Lord_Tyveris 2
·
0⤊
0⤋
a=1, b=2
replace in the equation
x= (1)(2)/2 (1+2-2)
x=2/2(1)
x=1(1)
x=1
2006-09-26 04:38:12
·
answer #7
·
answered by Minou 1
·
0⤊
0⤋
substituting values for a and b we get
x=ab/2(a+b-2)
=1*2/2(1+2-2)
=1(1)=1*1=1
answer=1
2006-09-26 01:45:11
·
answer #8
·
answered by KSA 3
·
0⤊
0⤋
given x=ab/2(a+b-2)
subsitute a=1 and b=2 then x becomes
x=1x2/2(1+2-2)
= 2/2(3-2)
=1x1
x =1
therefore x=1
2006-09-26 05:43:17
·
answer #9
·
answered by srirad 2
·
0⤊
0⤋
x = 1 * 2 / 2 * ( 1 + 2 - 2)
= 1 * 1
x = 1
2006-09-26 01:50:28
·
answer #10
·
answered by M. Abuhelwa 5
·
0⤊
0⤋